A Study on Positive and Negative Effects of Social Media on Society - W, Akram; Kumar, R (International Journal of Computer Sciences and Engineering, 2025)
Social media is a platform for public around the World to discuss their issues and opinions. Before knowing the actual aspects of social media people must have to know what does social media mean? Social media is a term used to describe the interaction between groups or individuals in which they produce, share, and sometimes exchange ideas, images, videos and many more over the internet and in virtual communities. Children are growing up surrounded by mobile devices and interactive social networking sites such as Twitter, MySpace, and Facebook, Orkut which has made the social media a vital aspect of their life. Social network is transforming the behavior in which youthful people relate with their parents, peers, as well as how they make use of technology. The effects of social networking are twofold.[1] On the positive side, social networks can act as invaluable tools for professionals. They achieve this by assisting young professionals to market their skills and seek business opportunities. Social networking sites may also be used to network efficiently. On the negative side, the internet is laden with a number of risks associated with online communities. Cyber bullying, which means a type of harassment that is perpetrated using electronic technology, is one of the risks. In this paper we cover every aspect of social media with its positive and negative effects. Focus is on the particular field like health, business, education, society and youth. During this paper we explain how these media will influence the society in a broad way.